2005
DOI: 10.1007/s11258-005-9049-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuum or zonation? Altitudinal gradients in the forest vegetation of Mt. Kilimanjaro

Abstract: Based on the analysis of 600 vegetation plots using the method of Braun-Blanquet (1964) the composition of the whole vascular forest plant flora with about 1220 species was studied in the forests of Mt. Kilimanjaro. The altitudinal distribution of all strata (trees, shrubs, epiphytes, lianas and herbs) along a transect of 2400 m is discussed with respect to altitudinal zonation and ecological factors. With unidimensionally constraint clustering significant discontinuities were revealed that occurred simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
309
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 294 publications
(348 citation statements)
references
References 50 publications
18
309
2
3
Order By: Relevance
“…It was generally taken as the average elevation of foothills in isolated mountains in the plain and hilly areas without intra-montane basins or valleys, e.g., Mt. Kilimanjaro (Hemp 2006). For oceanic islands such as Tenerife in the insular Spain, MBE is zero.…”
Section: Data Set For Intra-mountain Base Elevationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally taken as the average elevation of foothills in isolated mountains in the plain and hilly areas without intra-montane basins or valleys, e.g., Mt. Kilimanjaro (Hemp 2006). For oceanic islands such as Tenerife in the insular Spain, MBE is zero.…”
Section: Data Set For Intra-mountain Base Elevationmentioning
confidence: 99%
“…For example, the absolute height of Mt. Kilimanjaro is as high as 5895 m above sea level and it is even close to the equator, but the treeline is at about only 3500 m (Hemp 2006), about 1100~1400 m lower than in the interior Tibetan Plateau (Schickhoff 2005). The reason may be that it's a volcanic cone without intra-mountain plateaus or basins, and that mountain slopes are all completely exposed to the free air, so the temperature difference between the mountain surface and the free air at the same altitude may be very small.…”
Section: Introductionmentioning
confidence: 99%
“…The cloud forests are of great importance for watersheds in East Africa [15] [18]. In addition to the function of filtering and storing water, the upper montane and subalpine cloud forests have a high potential of collecting cloud water.…”
Section: Discussionmentioning
confidence: 99%
“…Mountainous areas are characterized by various types of vegetation which are found at different elevations and mountain flanks (Kitayama, 1992;Hemp, 2006). These different types of vegetation form a three-dimensional pattern in horizontal and altitudinal gradients.…”
Section: Introductionmentioning
confidence: 99%
“…He found that the vegetation landscape had a similar pattern to that in the latitudinal zone extending from the tropic to the pole (Sachs, 2003). Many studies have investigated vegetation types and patterns along altitudinal gradients in the mountains (Kitayama, 1992;Lovett, 1996;Kessler, 2000;Hemp, 2006). The three-dimensional pattern of vegetation landscapes are usually been related to the species diversity and distribution (Körner, 2000;Kitayama and Aiba, 2002;Wang el al., 2002;Bhattarai and Vetaas, 2003;Wang et al, 2007;Batllori et al, 2009;Sang, 2009 (Daniels and Veblen, 2003;Gian-Reto et al, 2005;Walther et al, 2005;Erschbamer et al, 2009;Odland, 2009;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%